2015
DOI: 10.5539/ass.v11n10p292
|View full text |Cite
|
Sign up to set email alerts
|

University Rankings as a Tool for Assessing the Quality of Education in the Context of Globalization

Abstract: Article is devoted to the new conditions for the development of society characterized by the reconstruction of the higher education and problem of increasing the competitiveness of Russian universities in the world. Global university rankings today are becoming indicators of the implementation of the integration process and competitive tool in the context of globalization of higher education. A characteristic feature of modern development is the transition to a new stage of the formation of an innovative socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 3 publications
0
14
0
2
Order By: Relevance
“…In this fast-changing higher education landscape, Europe 2020 agenda prescribes transformation of educational institutions, which requires major institutional, organizational and legislative reforms (Avralev and Efimova 2013;Erkkilä 2013;Jiao et al 2016). Such reforms either result from "best practice" or from intensive knowledge-based institutional connections and collaborations between government, universities, research centres, enterprises, associations and other stakeholders (Guerrero et al 2014;Jiao et al 2016).…”
Section: Results: Measurement Of University Competitiveness Within Rismentioning
confidence: 99%
“…In this fast-changing higher education landscape, Europe 2020 agenda prescribes transformation of educational institutions, which requires major institutional, organizational and legislative reforms (Avralev and Efimova 2013;Erkkilä 2013;Jiao et al 2016). Such reforms either result from "best practice" or from intensive knowledge-based institutional connections and collaborations between government, universities, research centres, enterprises, associations and other stakeholders (Guerrero et al 2014;Jiao et al 2016).…”
Section: Results: Measurement Of University Competitiveness Within Rismentioning
confidence: 99%
“…A different perspective on university rankings has indicated that importance of rankings is not going to reduce the importance (Goglio V., 2016) and how important are those results in research international recognition (Sombatsompop N. et al, 2011). University rankings as a tool for assessing the quality of education in the context of globalization is on research agenda for many researchers determining and designing policy directions for higher education quality improvement (Avralev N., Efimova I., 2015) and also aspects of university rankings and the reality (Williams R., Van Dyke N., 2008).…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…In Russia English is the only language that at least potentially can claim to be the second language (Avralev & Efimova, 2013). There are no other popular second languages in the country that seem to be embedded in Russia's almost monolingual languages habitats.…”
Section: Discussionmentioning
confidence: 99%